Tratamento endovascular de pacientes com doenças da aorta torácica: avaliação de resultados em longo prazo - Brandi, Antonio Carlos (2015)
Thoracic aortic diseases, including dissections, aneurysms, pseudoaneurysms among other, are serious conditions that bring serious risks of morbidity and mortality. Its incidence is low, but has been growing gradually due to the increase in life expectancy of the population, that in most cases, is associated with hypertension, smoking and diabetes mellitus. Advances in diagnostic techniques have also contributed to the identification of an increasing number of cases. The development of minimally invasive endovascular procedures has been used successfully in the treatment of these diseases, including patients with no indication for conventional surgical treatment. Objective: Evaluate the long-term results of endovascular treatment of patients with diseases of the thoracic aorta underwent implantation of self-expandable stent-grafts. Methods: This prospective study evaluated 112 patients who underwent percutaneous implantation of endoprosthesis of the thoracic aorta, from October 1998 to August 2013. Self-expandable endoprosthesis stent-graft Braile Biomédica ®, made of stainless steel and nitinol were employed. The occurrence of intraoperative and postoperative primary success, endoleaks, mortality, late evolution of the endoprosthesis and survival were evaluated in long term follow-up. Results: The mean time of the procedures was 72.66 ± 43.36 minutes (range 30-240 minutes). A total of 150 self-expandable stents were implanted in 112 patients, 61 (40.66%) of stainless steel and 89 (59.33%) of nitinol. The diameter and length of the stents of stainless steel and nitinol ranged from 24-45 mm (median 33) and 70-130 mm (median 90) 22-46 mm (median 35) and between 40 and 230 mm (median 110) respectively. The number of stents implanted per patient ranged from 1 to 4 (median 1). Primary success was observed in 100 (82.14%) of 112 patients treated. Immediate mortality occurred in seven (6.25%) patients, five (4.46%) from cardiovascular causes and two (1.78%) for non-cardiovascular causes. Late mortality occurred in 31 (27.68%) patients, 10 (8.93%) from cardiovascular causes, 12 (10.71%) for non-cardiovascular causes, two (1.78%) from natural causes-seven (6.25%) with no diagnosis. There hospital type I endoleaks occurred in four patients (3.57%), type II in five (4.46%) and three type IV (2.68%). Late endoleaks type I occurred in five (4.46%) patients and type IV in three (2.68%). Twenty-two patients (19.64%) had clinical complications in the immediate postoperative period, including nine (8.03%) pulmonary complications, four (3.57%) neurological abnormalities, three (2.67%) acute renal failure, two (1.78%) infections in the surgical incision, two (1.78%) with progression to post-implantation syndrome and one (0.89%) with laceration of the arterial access. Follow-up time ranged from 1 to 179 months (median 46). The acturial survival curve was 79,3% (IC95% 67,0-91,7) at 132 months free of death from cardiovascular causes. The logistic regression analysis showed that renal failure was the only risk factor that showed a statistically significant difference. Conclusions: The low levels of intra and postoperative complications demonstrate that the treatment is safe and effective. The high rate of survival after 132 months of follow-up for these critically ill patients show the benefits of endovascular technique to treatment of thoracic aorta diseases.